A conceptual model: Video-game engagement and its moderating impact on consumersâ personality - Abbasi, A.Z. (American Scientific Publishers, 2015)
Research on video-games has progressively increased since 2000, yet past studies are limited to explore the moderating role of video-game engagement in the collectivist society, especially in the context of Malaysia to investigate how video-game engagement influences consumersâ behavior in terms of their personality traits. Therefore, the contemporary study attempts to propose a conceptual model to examine how video-game engagement moderates the relationship between HEXACO personality traits and consumersâ personality. On basis of reviewing past studies, and their research issues, this study has suggested a distinctive conceptual model that has been proposed from traits theory of personality and engagement theory, particularly by taking the dimensions of HEXACO personality inventory model and one of the essences of engagement theory (learning through getting exposure of digital-framework) like video-game engagement as moderating variable. This paper has come up with the study propositions, which further requires future work to investigate them empirically. This study is unique in marketing to contribute in the field of consumer behavior by investigating the role of hedonic product as âvideo gameâ and its consumption as âengagementâ and examining its moderating influence on consumersâ personality. Â© 2015 American Scientific Publishers. All rights reserved.